ETIKA BISNIS ISLAM DALAM TRANSAKSI JUAL BELI PADA HOME INDUSTRY TAHU - Komarudin A; Aula Izatul Aini; Hanin Khofifah (Jurnal Ekonomi Syariah Darussalam, 2023)
In the district of Banyuwangi home industry or small industry is growing and developing rapidly. Banyuwangi has home industry centers, one of which is in Bagorejo Village, Srono District, Banyuwangi Regency. The purpose of this study was to determine the business ethics in buying and selling transactions at tofu home industry in Bagorejo Village, Srono District, Banyuwangi Regency in terms of Islamic Business Ethics. This study uses a qualitative method with a case study research type. As for this study using primary and secondary data sources. The data analysis technique used in this study is an interactive model. Home industry knows that Mr. Masduki and Mr. Mukhlis in Bagorejo Village, Srono District, Banyuwangi Regency have fully implemented Islamic Business Ethics. Because it is in accordance with the principles of unity, balance, free will, responsibility, and truth, virtue, and honesty. In contrast to home industry tofu, Mr. Habib Hasan, who is still unable to carry out Islamic Business Ethics. Due to having violated the principles of unity, balance and honesty, because Mr. Habib is still reducing the quantity of goods and hoarding merchandise before selling. It is better for tofu home industry traders to always uphold Islamic religious values. because with Islamic Business Ethics it will benefit all parties, both traders and consumers